THE IMPACT OF KNOWLEDGE PROCESSES AND CUSTOMER RELATIONSHIP MANAGEMENT (CRM) ON SERVICES QUALITY ALONG SUPPLY CHAIN - Al-Qaysi, Bilal .J.; Atallah Hussein, Hafsa (International Journal of Supply Chain Management, 2019)
This study summarizes a sample of the managers of the Iraqi cellular communications company with 84 employees. The company is a service organization responsible for providing integrated telecommunications services. As a management system that uses human, technical, material and financial resources, its size and value increase in line with technical progress. The demand for telecommunication services is increasing for several factors, the most important being the only means available to the majority and to the increase in population. The aim of this study is to develop and test a empirical model to link knowledge management processes and customer relationship management to the quality of services along supply chain. The problem of the study was formed through many mental and practical inquiries represented in the negotiation of the customer's knowledge and behavior, the importance of the horizon of customer relationship management, the level of its importance and its impact on the quality of services, the concept of quality of service, the level of its importance, the types of knowledge processes and their importance in the studied companies and their impact on Quality of services along supply chain. These questions were investigated later. The new study aimed at determining the relationship between the changes in the study in the company that was examined and the ability to apply it in all its parts and its ability to develop and use it to serve the customers in the examined organization. The study used the survey as a tool to collect the information that was diverted to be transferred because of statistical tools that were examined for results. The results and recommendations highlighted the reality and facts of the variables that the study addressed from the mental point of view and applied in the company's exams.